2010
DOI: 10.1080/00918360903543170
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Domestic Violence in Lesbian Relationships: Stereotypes and Gender Role Expectations

Abstract: In light of evidence suggesting that violence between lesbian couples is oftentimes dismissed as "mutually combative," expectations that support this perception were examined. Participants (N = 287) evaluated a domestic violence situation within the context of a lesbian partnership. As physical appearance may be used to support gender- and heterosexist-based stereotypes relating to lesbians, participants evaluated a domestic violence incident wherein the physical appearance of both the victim and perpetrator w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 36 publications
4
64
3
2
Order By: Relevance
“…The existence of an undetermined number of gay people worldwide and the fact that homosexuals and their respective relationships are often still closeted (Ali & Machado, 2005) creates challenges in determining the exact scope of this phenomena (Little & Terrance, 2010;Yu et al, 2013), which might have a greater reach and affect more people than what these studies have demonstrated.…”
Section: La Violência En Las Relaciones íNtimas De Personas Del Mismomentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of an undetermined number of gay people worldwide and the fact that homosexuals and their respective relationships are often still closeted (Ali & Machado, 2005) creates challenges in determining the exact scope of this phenomena (Little & Terrance, 2010;Yu et al, 2013), which might have a greater reach and affect more people than what these studies have demonstrated.…”
Section: La Violência En Las Relaciones íNtimas De Personas Del Mismomentioning
confidence: 99%
“…Indeed, the literature shows that this form of violence in intimate relationships can result in high costs for the health of the victim, leading, for example, to a greater propensity for the development of chronic pain and the development of many psychological problems such as depression and anxiety (Carvalho, Lewis, Derlega, Winstead, & Viggiano, 2011;Little & Terrance, 2010). The investigation of intimate partner violence began in the 1970s as a result of the social recognition of violence in intimate relationships, including violence against women in the family (Jasinski & Williams, 1998).…”
Section: La Violência En Las Relaciones íNtimas De Personas Del Mismomentioning
confidence: 99%
“…In general, female respondents have been found to rate incidents of IPV as more serious (Ahmed et al, 2013;Harris & Cook, 1994), more likely to sympathize with the victim regardless of gender of the abuser (Harris & Cook, 1994;, and attribute more blame and responsibility to assailants (Rhatigan et al, 2011). Little and Terrance's (2010) investigation of IPV among lesbian women found that female respondents perceived the dispute as more dangerous than male respondents. Researchers (Terrance, Plumm, & Thomas, 2011) have also found that male participants hold victims more responsible for their own victimization (particularly when they act passively) than female participants.…”
Section: Respondent Gender Differences In Perceptions Of Abusementioning
confidence: 99%
“…Efetivamente, a literatura comprova que esta forma de violência nas relações íntimas poderá apresentar custos elevados para a saúde das vítimas, conduzindo, por exemplo, a uma maior propensão para o desenvolvimento da dor crônica, ao desenvolvimento de diversos problemas psicológi-cos, como a depressão e a ansiedade (Carvalho, Lewis, Derlega, Winstead, & Viggiano, 2011;Little & Terrance, 2010).…”
Section: Palabras Clave: Violencia Relaciones Intimas Parejas Homosunclassified
“…Embora haja menor investimento científi co no estudo da violência nas relações íntimas na população homossexual, as evidências comprovam que este é um problema que não pode mais ser ignorado. A existência de um número indeterminado de pessoas homossexuais em todo o mundo, na medida em que, a homossexualidade e respectivos relacionamentos ainda são mantidos num sistema fechado (Antunes & Machado, 2005), impedem conhecer com exatidão a proporção deste fenômeno (Little & Terrance, 2010;Yu et al, 2013), que poderá ter um alcance maior e afetar muito mais indivíduos do que estes estudos têm vindo a demonstrar.…”
Section: Palabras Clave: Violencia Relaciones Intimas Parejas Homosunclassified